THE EFFECT OF VITAL CAPACITY OF THE LUNGS, NUTRITIONAL STATUS, PHYSICAL ACTIVITY AND EXERCISE MOTIVATION TOWARDS PHYSICAL FITNESS ON THE ATHLETE PACKAGE NATIONAL SPORTS COMMITTEE INDONESIA DEPOK CITY - Sujarwo, Sujarwo; Tangkudung, James; Hanif, Achmad Sofyan (Program Pascasarjana Universitas Negeri Jakarta, 2018)
The purpose of this study was to determine the effect of vital capacity of the lungs, nutritional status, physical activity and exercise motivation to physical fitness on the athlete Package National Sports Committee Indonesia Depok city.This research uses survey method to see the relationship between variables. Data analysis techniques use path pathology. Path analysis techniques can be used to test the direct and indirect effects on vital capacity of the lungs, nutritional status, physical activity and exercise motivation against Physical fitness the athlete package National sports Committee Indonesia Depok City.Overall, it can be concluded that after tested statistically to empirical data which have been obtained from field, it can be said that the four independent variables namely vital capacity of lungs, nutritional status, physical activity and exercise motivation have significant direct positive influence of physical fitness on on the athlete package National Sports Committee Indonesia Depok city.   Keywords: vital capacity of the lungs, nutritional status, physical activity, exercise motivation and physical fitness